Effect Of Total Assets, Receivables And Inventories Turnover On Roa In Retail Trading Companies Indonesia Stock Exchange (Idx) - Bakir, Baharuddin; Sadersah, Lugas (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The purpose of this study to determine the effect of total asset turnover, accounts receivable turnover and inventory turnover on ROA. The population in this study is the retail trade sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling and 12 companies were obtained as samples. The data collection technique is by downloading financial reports on the Indonesian Stock Exchange website. For instrument testing using the Classical Assumption Test while for data techniques using Multiple Linear Regression Analysis. The results of statistical tests from the results of the F Test (Simultaneous) show that Total Asset Turnover (X1), Accounts Receivable Turnover (X2) and Inventory Turnover (X3) have a significant effect on ROA (Y). The statistical test results from the results of the T (Partial) Total Asset Turnover Test (X1) have a significant positive effect on ROA (Y). While Accounts Receivable Turnover (X2) and Inventory Turnover (X3) have a significant negative effect on ROA (Y).Â